The Interrelationships Between Hybrid Work, Employee Performance And Organizational Culture At The Workplace: A Conceptual Framework - Sharifah Zeenatu Zainab binti Syed Zakaria; Khairunneezam Mohd Noor; Mashitah Sulaiman (Yayasan Dakwah Islamiah Malaysia, 2026)
Non-Indexed Publication